PENGARUH LITERASI KEUANGAN, ORIENTASI PASAR DAN INOVASI PRODUK TERHADAP KINERJA UMKM PADA PELAKU USAHA KULINER DI KOTA METRO - Galia Intan Suri Mahardika; Angga Kurniawan; Elmira Febri Darmayanti (RISTANSI: Riset Akuntansi, 2023)
This study aimed at analyzing financial literacy (1), market orientation (2), and product innovation (3) on the performance of small and medium enterprises (SMEs) in culinary business actors in Metro City. This type of research used quantitative research method. The data used in this research were primary data, data collection were distributed through questionnaires to culinary business actors as many as 980 respondents. The sampling technique in this study was in slovin formula and the research sample criteria in order to obtain a research sample was 98 respondents. The results showed that financial literacy had a positive and significant effects on small and medium enterprise (SME) performance, market orientation had a positive and significant effect on SME performance, and product innovation had a positive and significant effect on SME performance. Then, in the F test (model test) the results showed that financial literacy, market orientation and product innovation had positive effects on the performance of SMEs in culinary businesses in Metro City.